Syn-deformation temperature and fossil fluid pathways along an exhumed detachment zone, khao khwang fold-thrust belt, Thailand - Rowan L. Hansberry (2018)
© 2015 Elsevier B.V. Shale detachment zones, their influence on deformational style, and their internal mechanisms of deformation are an understudied aspect of fold-thrust belts. Properties such as deformational temperature, lithology, and mineralogy are often recognized as having a key influence on the rheology and deformational style of detachment zones and overlying fold-thrust belts. However, little work has been conducted on rock properties of known detachment zones. A recently described upper-level detachment zone in the exhumed Khao Khwang Fold-Thrust Belt of central Thailand provides an ideal natural laboratory for investigation of the deformation conditions of the detachment zone, and association with its complex deformational style. The low-grade metamorphic indicator illite crystallinty is used to broadly constrain deformational temperatures, while oxygen and carbon stable isotope analysis provides insight into fluid flow history and fluid-rock interaction. Illite crystallinity data indicate deep diagenetic, to low anchizonal conditions, and temperatures of ~160-210 °C in the shale detachment, interpreted as reflecting peak metamorphic conditions during the Triassic Indosinian Orogeny. No trend between the intensity (spacing, complexity) of structures and illite crystallinty is observed. However, shale shear zones of continuous-style deformation and inferred higher finite strain display uniformly higher illite crystallinty than surrounding packages of discontinuously faulted shales. We also note a positive association between total organic carbon content in the shales and the spacing and complexity of deformational structures. Data from limestones and syn-tectonic vein fills detail the history of fluid-rock interaction during early mesogenesis, through to orogenesis. The early covariant trend of increasingly negative δ 13 C and δ 18 O values is attributed to increasing burial, while a divergent orogenic trend of increasingly negative δ 18 O values is interpreted as the result of a loss of matrix permeability and interruption of fluid-rock re-equilibration. These hottest fluids were concentrated along large thrusts which facilitated fluid movement during orogenesis.